Preparation method of epoxy resin wave-absorbing composite material, composite material and application

By introducing halide-type ionic liquids and gallium-indium alloy liquid metals into epoxy resin, the prepared epoxy resin absorbing composite material solves the problems of impedance matching and environmental stability, achieves broadband absorption and good mechanical properties, and is suitable for electromagnetic shielding and stealth coatings.

CN122325934APending Publication Date: 2026-07-03SICHUAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610707880.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-21
Publication Date
2026-07-03

AI Technical Summary

Technical Problem

Existing epoxy resin absorbing materials suffer from problems such as difficulty in impedance matching, poor environmental stability, high processing difficulty, poor dispersibility, and weak mechanical properties, which limit their application in electromagnetic shielding of electronic equipment and stealth coatings for aerospace.

Method used

An epoxy resin microwave absorbing composite material was prepared by using halide-type ionic liquids and gallium-indium alloy liquid metal as additives through physical blending and room temperature curing. The unique anion and cation structure of the ionic liquid and the high conductivity of the gallium-indium alloy were utilized to optimize the electromagnetic parameter matching. Furthermore, the interfacial bonding was enhanced through non-covalent modification, and the dispersibility and environmental stability were improved.

Benefits of technology

It achieves wideband absorption capability and good mechanical properties, making it suitable for electromagnetic shielding of electronic equipment and stealth coatings for aerospace applications. It solves the shortcomings of traditional materials in terms of environmental stability and performance uniformity, and simplifies the processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122325934A_ABST
    Figure CN122325934A_ABST
Patent Text Reader

Abstract

This application discloses a method for preparing an epoxy resin microwave absorbing composite material, the composite material itself, and its applications, belonging to the field of electromagnetic functional composite materials. The method includes dissolving a halide-type ionic liquid precursor and a salt containing a target anion in a solvent, stirring at room temperature, removing the precipitate to obtain a filtrate, removing the solvent to obtain the target ionic liquid; blending gallium and indium particles, heating to obtain molten gallium-indium liquid metal, removing the surface oxide film from the molten gallium-indium liquid metal to form a uniformly dispersed gallium-indium alloy liquid metal; mixing epoxy resin and a curing agent in a preset ratio, adding the target ionic liquid and the gallium-indium alloy liquid metal, stirring under ultrasonic conditions until completely mixed to obtain a mixed solution; pouring the mixed solution into a mold, curing at room temperature, and demolding to obtain the epoxy resin microwave absorbing composite material. This application can solve the problems of difficult impedance matching control, poor environmental stability, high processing difficulty, poor dispersibility, and weak mechanical properties in microwave absorbing materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of electromagnetic functional composite materials technology, and in particular to a method for preparing an epoxy resin microwave absorbing composite material, the composite material, and its application. Background Technology

[0002] With the rapid development of electronic information technology, microwave absorbing materials, as functional materials that can effectively absorb and attenuate incident electromagnetic waves, have an urgent application demand in fields such as electromagnetic compatibility of electronic equipment, radiation protection of communication base stations, and stealth coatings for aerospace vehicles. An ideal microwave absorbing material should have the characteristics of being "thin, light, wide, and strong," that is, thin, lightweight, with a wide absorption bandwidth and strong absorption capacity, while also taking into account good mechanical properties and environmental adaptability.

[0003] Existing insulating microwave absorbing materials are generally constructed by introducing specific functional components into an insulating matrix. The core components are typically nano-metal particles, piezoelectric materials, or other easily polarized functional components to build the absorbing system. The main absorption mechanism is polarization loss. Specifically, when electromagnetic waves are incident on the material, these easily polarized components undergo various polarization behaviors under the influence of an alternating electric field, including electronic polarization, ionic polarization, dipole reorientation polarization, and interfacial polarization. Through charge migration, relaxation, and energy dissipation during polarization, the electromagnetic energy of the electromagnetic wave is converted into other forms of energy such as heat, thereby achieving absorption and attenuation of the electromagnetic wave. At the same time, relying on the high resistivity of the insulating matrix, the material is ensured to be non-conductive, avoiding electromagnetic wave reflection, making it suitable for microwave absorbing scenarios such as electronic devices and precision instruments that require insulation performance.

[0004] The practical application of insulating and absorbing materials in aerospace, outdoor electronic equipment, and extreme environment engineering still faces significant challenges: First, the frequency band performance is limited, with most materials only able to achieve absorption in a single frequency band, resulting in insufficient effective bandwidth and difficulty in covering the broadband requirements of complex electromagnetic environments; second, there are defects in structural stability, with poor compatibility between polarization components and insulating matrix, relying on physical blending leading to weak interfacial bonding, which easily causes component aggregation, migration, and irreversible performance degradation during long-term use. In addition, some polarization components are prone to oxidation, further exacerbating performance fluctuations; third, there is insufficient environmental tolerance, with traditional matrices and polarization components having limited resistance to high and low temperatures, damp heat, and ultraviolet aging. In outdoor or extreme environments, matrix cracking and delamination, and component failure are prone to occur, resulting in a sharp drop in absorption performance and a shortened lifespan.

[0005] Due to its excellent adhesion, mechanical strength, chemical resistance, and ease of processing, epoxy resin has become a key factor in addressing the aforementioned challenges in the development of epoxy resin-based microwave absorbing composites, leading to their increasingly widespread application. Epoxy resin-based microwave absorbing composites have significant applications in electromagnetic wave absorption, such as in radar stealth technology, electronic equipment shielding, and protective coatings, effectively reducing electromagnetic interference and improving system performance.

[0006] In practice, to impart microwave absorption properties to epoxy resin, various lossy fillers are typically added. These fillers mainly include carbon-based materials (such as graphene and carbon nanotubes), magnetic particles (such as ferrite and metal alloy particles), conductive polymers (such as polyaniline and polypyrrole), and novel lossy agents (such as piezoelectric materials). These fillers, by being combined with the epoxy resin matrix, utilize its polarization or conductivity to achieve the absorption and attenuation of electromagnetic waves.

[0007] Existing epoxy resin microwave absorbing materials have significant drawbacks: carbon-based materials face challenges such as difficulty in impedance matching, poor environmental stability (susceptibility to humidity and heat), high processing difficulty (e.g., uneven dispersion), and insufficient performance uniformity; magnetic particles suffer from high density (increasing material weight), rapid high-frequency loss attenuation (limiting high-frequency applications), easy oxidation (reducing long-term environmental stability), and poor dispersion (affecting uniformity); conductive polymers are characterized by difficulty in controlling conductivity (difficulty in precisely controlling conductivity), poor environmental stability (easy aging), and weak mechanical properties (reducing overall material strength). These shortcomings severely limit the reliability and development potential of these materials in electromagnetic shielding of electronic devices, microwave absorbing applications, and aerospace stealth coatings. Summary of the Invention

[0008] This application provides a method for preparing epoxy resin microwave absorbing composite materials, the composite material itself, and its applications. This method addresses the problems of existing epoxy resin microwave absorbing materials, such as difficulty in controlling impedance matching, poor environmental stability, high processing difficulty, poor dispersibility, and weak mechanical properties.

[0009] To achieve the above objectives, the technical solution of this invention is as follows: In a first aspect, embodiments of the present invention provide a method for preparing an epoxy resin microwave absorbing composite material, comprising: The precursor of the halide-type ionic liquid and the salt containing the target anion are dissolved in a solvent. After stirring at room temperature for 6-10 hours, the precipitate is removed to obtain a filtrate. The solvent is removed from the filtrate to obtain the target ionic liquid. Gallium particles and indium particles are blended and melted at 80~90℃ for 0.5~2h to obtain molten gallium-indium liquid metal. The surface oxide film of the molten gallium-indium liquid metal is removed to form a uniformly dispersed gallium-indium alloy liquid metal. Epoxy resin and epoxy resin curing agent are mixed in a preset ratio, and then the target ionic liquid and the gallium indium alloy liquid metal are added. The mixture is stirred under ultrasonic conditions for 5 to 10 minutes until it is completely mixed to obtain a mixed solution. The mixed solution was poured into a mold and cured at room temperature for 8-12 hours. After demolding, an epoxy resin microwave absorbing composite material was obtained.

[0010] In conjunction with the first aspect, in one possible implementation, the molar ratio of the halide-type ionic liquid precursor to the salt containing the target anion is 1:(1.1~1.2).

[0011] In conjunction with the first aspect, in one possible implementation, the mass ratio of the gallium particles to the indium particles is (2~4):1.

[0012] In conjunction with the first aspect, in one possible implementation, the mass fraction of the target ionic liquid in the epoxy resin is 5% to 20%.

[0013] In conjunction with the first aspect, in one possible implementation, the mass fraction of the gallium-indium alloy liquid metal in the epoxy resin is 40% to 60%.

[0014] In conjunction with the first aspect, in one possible implementation, the halide-type ionic liquid precursor is one of 1-butyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-ethyl-3-methylimidazolium dicyandiamide, 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, and N-methylimidazolium chloride.

[0015] In conjunction with the first aspect, in one possible implementation, the salt containing the target anion is one of sodium bis(trifluoromethanesulfonyl)imide, sodium p-toluenesulfonate, and sodium methanesulfonate.

[0016] In conjunction with the first aspect, in one possible implementation, the solvent is one of deionized water, methanol, and anhydrous acetonitrile.

[0017] Secondly, another embodiment of the present invention provides an epoxy resin microwave absorbing composite material, which is prepared by the above-described method for preparing epoxy resin microwave absorbing composite materials.

[0018] Thirdly, another embodiment of the present invention provides the application of epoxy resin absorbing composite material in the field of electromagnetic shielding of electronic devices, absorbing materials and aerospace stealth coatings.

[0019] One or more technical solutions provided in the embodiments of the present invention have at least the following technical effects or advantages: The method for preparing epoxy resin microwave absorbing composite materials provided in this application uses epoxy resin as a matrix and introduces a target ionic liquid and gallium indium alloy liquid metal as a specific additive system. First, a physical blending and room temperature curing process is employed. Then, the target ionic liquid is doped, ultrasonically dispersed, compounded with epoxy resin and a curing agent, and cured at a constant temperature to obtain the composite material. This method utilizes the unique anion and cation structure and tunable dielectric properties of the target ionic liquid, combined with the high conductivity and fluidity of the gallium indium alloy liquid metal, to jointly optimize the electromagnetic parameter matching of the composite material. This solves the problem of difficult impedance matching control in carbon-based materials and improves the limitations of rapid high-frequency loss attenuation and narrow bandwidth of magnetic particles. Meanwhile, the target ionic liquid, through non-covalent modification, forms a stable interface layer between the filler and the resin matrix, significantly enhancing the dispersibility and interfacial bonding of the gallium-indium alloy liquid metal. This overcomes the defects of carbon-based materials, magnetic particles, and conductive polymers, such as uneven dispersion, insufficient performance uniformity, and weak interfacial bonding leading to weak mechanical properties. Furthermore, the extremely low vapor pressure, high thermal stability, and chemical stability of the target ionic liquid, combined with the non-oxidizing properties of the gallium-indium alloy liquid metal, synergistically improve the overall environmental stability of the composite material, enhancing its resistance to damp heat and aging, effectively solving the problem of poor environmental stability in traditional materials. This process is simple, avoiding complex processing, and is conducive to large-scale production. The resulting composite material achieves excellent microwave absorption performance (such as broadband absorption capability) while maintaining good mechanical properties, making it suitable for electromagnetic shielding of electronic equipment, broadband microwave absorption, and aerospace stealth coatings, providing a reliable and efficient solution. Attached Figure Description

[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments of the present invention or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0021] Figure 1 Scanning electron microscope image of the epoxy resin microwave absorbing composite material prepared by the preparation method of Example 1 of this application; Figure 2 The resistivity of the epoxy resin microwave absorbing composite material prepared by the preparation methods of Examples 1-1, 1-2, 1-3 and 1-4 of this application; Figure 3 The resistivity of the epoxy resin microwave absorbing composite material prepared by the preparation methods of Examples 1-4, 1-5, and 1-6 of this application; Figure 4 The resistivity of the epoxy resin microwave absorbing composite material prepared by the preparation methods of Examples 1-4, 1-9, and 1-10 of this application; Figure 5 The maximum reflection loss of the epoxy resin microwave absorbing composite material prepared by the preparation methods of Examples 1-1, 1-2, 1-3, and 1-4 of this application; Figure 6 The maximum reflection loss of the epoxy resin microwave absorbing composite material prepared by the preparation methods of Examples 1-4, 1-5, and 1-6 of this application; Figure 7 The maximum reflection loss of the epoxy resin microwave absorbing composite material prepared by the preparation methods of Examples 1-4, 1-7, and 1-8 of this application; Figure 8 The real and imaginary parts of the average dielectric parameters of the epoxy resin microwave absorbing composite materials prepared by the preparation methods of Examples 1-1, 1-2, 1-3 and 1-4 of this application; Figure 9 The real and imaginary parts of the average dielectric parameters of the epoxy resin microwave absorbing composite materials prepared by the preparation methods of Examples 1-4, 1-5, and 1-6 of this application are shown. Figure 10 The real and imaginary parts of the average dielectric parameters of the epoxy resin microwave absorbing composite materials prepared by the preparation methods of Examples 1-7, 1-4, and 1-8 of this application are shown. Figure 11 The tensile strength of the epoxy resin microwave absorbing composite materials prepared by the preparation methods of Examples 1-1, 1-2, 1-3 and 1-4 of this application. Detailed Implementation

[0022] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of this application. All other embodiments obtained by those skilled in the art based on the embodiments of this application without creative effort are within the scope of protection of this application.

[0023] In the relevant descriptions of this embodiment, the terms "including," "containing," and "possessing" are all open terms and are generally understood to include but not be limited to; the term "at least one" is generally understood to mean one or more, where "multiple" refers to two or more; the term "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single or multiple items, for example, "at least one of a, b, or c", or "at least one of a, b, and c", which can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple; the symbol "A / B" is used to describe the selection relationship of associated objects, generally indicating an "or" relationship.

[0024] In the following description of the embodiments, the terminology used in the embodiments of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. The singular forms "a" and "the" as used in the embodiments of this application and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.

[0025] Those skilled in the art should understand that, in the following description of the embodiments of this application, the sequence of numbers does not imply the order of execution. Some or all steps may be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.

[0026] Those skilled in the art will understand that the numerical ranges in the embodiments of this application should be understood to specifically disclose each intermediate value between the upper and lower limits of the range. Each smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included within the scope of this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0027] Unless otherwise stated, the technical / scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains. While this application describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this application. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0028] This invention provides a method for preparing an epoxy resin microwave absorbing composite material, comprising: Step 1: Dissolve the halide-type ionic liquid precursor and the salt containing the target anion in a solvent. Stir at room temperature for 6-10 hours (typical but not limiting times such as 6, 7, 8, 9, and 10 hours are acceptable) to remove the precipitate and obtain a filtrate. Remove the solvent from the filtrate to obtain the target ionic liquid. This completes the preparation of the target ionic liquid. Specifically, after stirring at room temperature for 6-10 hours, remove the precipitate by vacuum filtration to obtain a filtrate. Rotary evaporate the filtrate at 30-40°C (typical but not limiting temperatures such as 30°C, 35°C, and 40°C are acceptable) and then vacuum dry it at 80-100°C (typical but not limiting temperatures such as 80°C, 85°C, 90°C, 95°C, and 100°C are acceptable, preferably 80°C) under a vacuum degree ≤0.01 MPa to remove the solvent and obtain the target ionic liquid.

[0029] Step 2: Gallium and indium particles are blended and melted at 80-90℃ (typical but not limiting temperatures such as 80℃, 85℃, and 90℃) for 0.5-2 hours (typical but not limiting times such as 0.5h, 1h, 1.5h, and 2h) to obtain molten gallium-indium liquid metal. The surface oxide film of the molten gallium-indium liquid metal is then removed to form a uniformly dispersed gallium-indium alloy liquid metal. This is the preparation of gallium-indium alloy liquid metal. Specifically, molten gallium-indium liquid metal is obtained by melting and stirring at 80-90℃ for 0.5-2 hours. The liquid metal is then broken up by ultrasonic treatment using a cell disruptor for 30-60 minutes (typical but not limiting times such as 30min, 40min, 50min, and 60min) to remove the surface oxide film and form a uniformly dispersed gallium-indium alloy liquid metal. During the melting process, an oxide film will appear on the surface of the molten gallium-indium liquid metal. This oxide film has insulating properties and will block conductivity. Furthermore, without breaking down the oxide film, the molten gallium-indium liquid metal lacks dispersibility or exhibits very poor dispersion. Therefore, a cell disruptor is used to break down the oxide film on its surface, thereby removing the surface oxide film.

[0030] Furthermore, the ultrasonic power of the cell disruptor is 60-90% (typical but not limiting ultrasonic powers such as 60%, 70%, 80% and 90%).

[0031] Step 3: Mix the epoxy resin and epoxy resin curing agent according to a preset ratio, then add the target ionic liquid and gallium-indium alloy liquid metal, and stir under ultrasonic conditions for 5-10 minutes (typical but not limiting times such as 5 min, 6 min, 7 min, 8 min, 9 min, and 10 min can be used). Continue stirring until a mixed solution is obtained. Further, the preset ratio of epoxy resin and epoxy resin curing agent in the preset ratio is 2:1. The thickness of the epoxy resin is 2.0-2.5 mm (typical but not limiting thicknesses such as 2.0 mm, 2.1 mm, 2.2 mm, 2.3 mm, 2.4 mm, and 2.5 mm can be used), preferably 2.1-2.3 mm.

[0032] Step 4: Pour the mixed solution into the mold and cure at room temperature for 8-12 hours (typical but not limiting times can be 8h, 9h, 10h, 11h, and 12h, etc.). After demolding, the epoxy resin microwave absorbing composite material is obtained. The room temperature is 15-25℃.

[0033] The method for preparing epoxy resin microwave absorbing composite materials provided in this application uses epoxy resin as a matrix and introduces a target ionic liquid and gallium indium alloy liquid metal as a specific additive system. First, a physical blending and room temperature curing process is employed. Then, the target ionic liquid is doped, ultrasonically dispersed, compounded with epoxy resin and a curing agent, and cured at a constant temperature to obtain the composite material. This method utilizes the unique anion and cation structure and tunable dielectric properties of the target ionic liquid, combined with the high conductivity and fluidity of the gallium indium alloy liquid metal, to jointly optimize the electromagnetic parameter matching of the composite material. This solves the problem of difficult impedance matching control in carbon-based materials and improves the limitations of rapid high-frequency loss attenuation and narrow bandwidth of magnetic particles. Meanwhile, the target ionic liquid, through non-covalent modification, forms a stable interface layer between the filler and the resin matrix, significantly enhancing the dispersibility and interfacial bonding of the gallium-indium alloy liquid metal. This overcomes the defects of carbon-based materials, magnetic particles, and conductive polymers, such as uneven dispersion, insufficient performance uniformity, and weak interfacial bonding leading to weak mechanical properties. Furthermore, the extremely low vapor pressure, high thermal stability, and chemical stability of the target ionic liquid, combined with the non-oxidizing properties of the gallium-indium alloy liquid metal, synergistically improve the overall environmental stability of the composite material, enhancing its resistance to damp heat and aging, effectively solving the problem of poor environmental stability in traditional materials. This process is simple, avoiding complex processing, and is conducive to large-scale production. The resulting composite material achieves excellent microwave absorption performance (such as broadband absorption capability) while maintaining good mechanical properties, making it suitable for electromagnetic shielding of electronic equipment, broadband microwave absorption, and aerospace stealth coatings, providing a reliable and efficient solution.

[0034] The preparation method of this invention introduces a target ionic liquid with a specific function and a gallium-indium alloy liquid metal into an epoxy resin matrix, forming an innovative composite material system. Ionic liquids, as room-temperature molten salts composed of organic cations and inorganic / organic anions, possess characteristics such as extremely low vapor pressure, high thermal stability, strong designability, and good conductivity. The preparation method of this application creatively uses them as key interface modifiers and performance enhancers. Utilizing their unique amphiphilic structure, a stable "ionic liquid interface layer" is formed within the epoxy resin doped with liquid metal filler through non-covalent interactions. This interface layer effectively blocks direct contact between filler particles, preventing their re-aggregation, thereby significantly improving the dispersibility of the gallium-indium alloy liquid metal in the resin matrix and strengthening the interfacial bonding between the filler and the matrix. Simultaneously, the liquid metal, with its unique liquid flowability and high conductivity, not only facilitates the construction of a conductive network in the composite material but also provides conditions for inducing multiple polarizations (such as interfacial polarization).

[0035] Regarding electromagnetic functionality, the preparation method of this application constructs a multi-layered, synergistic electromagnetic loss mechanism, effectively overcoming the limitations of traditional materials that rely on a single loss mechanism. The ionic conductivity of the ionic liquid itself, along with the delocalized π-electron system in its structure, works synergistically with the conductive network of the gallium-indium alloy liquid metal to construct a rich hierarchy of polarization and loss centers within the composite material. More importantly, the introduction of the ionic liquid allows for precise control of the complex permittivity of the composite material. By changing the type and amount of ionic liquid, the electromagnetic parameters of the material can be optimized, making its characteristic impedance closer to the free-space wave impedance. This significantly reduces the reflectivity of electromagnetic waves on the material surface, allowing more electromagnetic waves to enter the material and be dissipated, ultimately achieving a broadband, strong absorption effect and optimizing impedance matching characteristics.

[0036] In terms of preparation process, the preparation method of this application provides a green, simple route that is highly compatible with existing processes. It employs physical blending and solvent-free ultrasonic dispersion throughout, avoiding the use of organic solvents in traditional methods, making it more environmentally friendly and safer. The addition of ionic liquids not only does not increase the initial viscosity of the epoxy resin system, but also improves the processing fluidity of the composite slurry with high gallium-indium alloy liquid metal filler content due to its lubricating and diluting effects, making it easier to cast, coat, or pot. Combined with room temperature curing, this process allows for easy control of product thickness and dimensions by adjusting process parameters and mold morphology, offering advantages such as simple process, low cost, and scalable production.

[0037] Ultimately, through the non-covalent modification of the ionic liquid, interface enhancement, and synergistic effect with the liquid metal, the epoxy resin microwave absorbing composite material prepared by the method of this application exhibits outstanding microwave absorption performance while maintaining good mechanical properties and processability. Examples demonstrate that this composite material can achieve a maximum reflection loss as low as -51.3 dB, achieving excellent electromagnetic wave absorption performance.

[0038] Further, the molar ratio of the halide-type ionic liquid precursor to the salt containing the target anion is 1:(1.1~1.2) (typical but not limiting molar ratios such as 1:1.1, 1:1.15, and 1:1.2 are acceptable). Preferably, the molar ratio of the halide-type ionic liquid precursor to the salt containing the target anion is 1:1.2. This ensures that the anion exchange reaction proceeds fully, the halide-type ionic liquid precursor and the salt containing the target anion are thoroughly mixed, maximizing the generation of the target ionic liquid with the desired structure, maximizing the yield, and effectively reducing the residual precursor salt, thereby ensuring the purity and performance consistency of the final target ionic liquid. In Example 1, the target ionic liquid was successfully prepared using a molar ratio of 1:1.2. Establishing this ratio range allows the synthesized target ionic liquid to have a predictable and stable chemical structure and dielectric properties, laying a reliable foundation for its use as a performance enhancer in subsequent composite steps and for precisely controlling the electromagnetic parameters of composite materials, effectively solving the problem of uncontrollable electromagnetic properties of materials caused by fluctuations in additive performance.

[0039] Optionally, the mass ratio of gallium particles to indium particles is (2~4):1 (typical but not limiting mass ratios such as 2:1, 3:1, and 4:1 are possible). This ratio is key to forming a gallium-indium alloy liquid metal with suitable fluidity and surface properties. Preferably, the mass ratio of gallium particles to indium particles is 3:1. As in Example 1, a mass ratio of 3:1 was used, and the mixture was melted at 85°C. Alloys within this ratio range can ensure the formation of a stable eutectic liquid metal with moderate fluidity. The oxide film formed on the surface is more easily and effectively removed during subsequent ultrasonic disruption treatment (such as using a cell disruptor), resulting in a well-dispersed liquid metal filler. Background art points out that magnetic particles have the problem of "poor dispersibility," while this preferred gallium-indium ratio optimizes the physical properties of the filler from the source, making it easier to achieve uniform and stable dispersion in the epoxy resin matrix, avoiding defects such as performance inhomogeneity and mechanical weakness caused by filler agglomeration or uneven dispersion.

[0040] Furthermore, the mass fraction of the target ionic liquid in the epoxy resin is 5% to 20% (typical but not limiting mass fractions such as 5%, 10%, 15%, and 20%). This content range is a performance optimization range verified through numerous experiments, as shown in Examples 1-7, 1-4, and 1-8, which correspond to addition amounts of 5%, 10%, and 20%, respectively. Figure 7 and Figure 10 Relevant test data show that within this range, the addition of the target ionic liquid can effectively improve the dielectric parameters and microwave absorption performance of the composite material (reducing the maximum reflection loss), while the mechanical properties of the material are also maintained or improved. Figure 11This range precisely balances performance enhancement with cost and process feasibility. If the content is too low (below 5%), the interface modification and polarization enhancement effects are not significant; if the content is too high (above 20%), it may negatively affect the curing process or mechanical properties of the composite material. This range effectively solves the problem of "high processing difficulty (such as uneven dispersion)" in the prior art, and optimizes the dispersibility and interfacial bonding of the filler by using an appropriate amount of ionic liquid, thereby ensuring the uniformity and stability of material properties.

[0041] Furthermore, the mass fraction of gallium-indium alloy liquid metal in the epoxy resin is 40%~60% (typical but not limiting mass fractions such as 40%, 45%, 50%, 55%, and 60%). This range is the core filler content window for achieving excellent microwave absorption performance. This is in conjunction with Examples 1-5 (40%), 1-4 (50%), 1-6 (60%), and... Figure 3 , 6 The test results of 9 show that when the content is in this range, the composite material can build a sufficiently dense but not overloaded conductive network, thereby achieving the best impedance matching and electromagnetic loss balance. Figure 6 The absorption performance is optimal in this range. Figure 9 This indicates that the average dielectric parameter exhibits a peak value within this range. This limitation directly addresses the problems of "high density" of magnetic particles and "difficulty in impedance matching" of carbon-based materials in the background technology. Under the premise of ensuring that the material density is not excessively increased, the composite material achieves efficient wave absorption in a specific frequency band by optimizing the content of conductive filler. This avoids the performance degradation caused by insufficient filler or the increased reflectivity, processing difficulties, and cost increases caused by excessive filler.

[0042] Optionally, the halide-type ionic liquid precursor is one of 1-butyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-ethyl-3-methylimidazolium dicyandiamide, 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, and N-methylimidazolium chloride. These specific halide-type ionic liquid precursor selections provide a clear and feasible starting material route for synthesizing target ionic liquids with specific cation structures. Examples 1-4, 1-9, and 1-10 respectively used different halide-type ionic liquid precursors (such as 1-butyl-3-methylimidazolium chloride, etc.). Figure 4 The resistance test results show that the ionic liquids prepared using different precursors have little effect on the resistance value of the composite material, indicating that these optional precursors are universal in maintaining the basic conductivity properties of the composite material. This effective ionic liquid precursor provides a specific and operable chemical material selection for implementing this invention, ensuring the repeatability and industrialization potential of the preparation method, and guaranteeing the reliability of the final composite material performance from the raw material level.

[0043] Optionally, the salt containing the target anion is one of sodium bis(trifluoromethanesulfonyl)imide, sodium p-toluenesulfonate, and sodium methanesulfonate. Together with the aforementioned halide-type ionic liquid precursors, they define the anion source of the target ionic liquid. By selecting these specific anionic salts, functional anions such as bis(trifluoromethanesulfonyl)imide, p-toluenesulfonate, and methanesulfonate can be introduced, thereby endowing the final synthesized target ionic liquid with different polarities, hydrophobicities, and thermal stability. The above-mentioned salts were used for synthesis in the examples. Different anions affect the compatibility, ion mobility, and polarization ability of the ionic liquid in the epoxy resin matrix, thus allowing for fine control of the dielectric constant of the composite material (e.g., the real and imaginary parts of the dielectric constant, see...). Figure 8 , 10 This provides a key means to address the problems of "difficult impedance matching" in carbon-based materials and "difficult conductivity" in conductive polymers in the background technology.

[0044] Optionally, the solvent can be one of deionized water, methanol, and anhydrous acetonitrile. This solvent can effectively dissolve the halide-type ionic liquid precursor and the salt containing the target anion, promoting the anion exchange reaction between them. Examples 1, 2, and 3 used deionized water, methanol, and anhydrous acetonitrile, respectively, demonstrating the universality of the method. This limitation eliminates the need for special, expensive, or difficult-to-handle solvents in the synthesis of the target ionic liquid, simplifies post-processing (such as solvent removal), reduces preparation costs and environmental burden, and improves process safety. From a production implementation perspective, it solves the problem of "high processing difficulty" mentioned in the background technology, making the entire preparation method greener, more economical, and easier to scale up, thus enhancing the industrial application value of this technical solution.

[0045] Another embodiment of the present invention provides an epoxy resin microwave absorbing composite material, which is prepared by the above-described method for preparing epoxy resin microwave absorbing composite materials.

[0046] Another embodiment of the present invention provides the application of epoxy resin absorbing composite material in the field of electromagnetic shielding of electronic equipment, absorbing materials and aerospace stealth coatings.

[0047] To ensure that the above-described implementation details and operations of this application can be clearly understood by those skilled in the art, and to highlight the significant advancements in the preparation method of the epoxy resin microwave absorbing composite material of this application, the following examples illustrate the above technical solutions.

[0048] Example 1 A halide-type ionic liquid precursor with a molar ratio of 1:1.2 was dissolved in a solvent along with a salt containing the target anion. After stirring at room temperature for 8 hours, the precipitate was removed by vacuum filtration to obtain a filtrate. The filtrate was then rotary evaporated at 40°C and vacuum dried at 80°C under a vacuum degree ≤0.01 MPa to remove the solvent, yielding the target ionic liquid. The halide-type ionic liquid precursor was 1-butyl-3-methylimidazolium chloride. The salt containing the target anion was sodium bis(trifluoromethanesulfonyl)imide. The solvent was deionized water.

[0049] Step 2: Gallium particles and indium particles with a mass ratio of 3:1 are mixed, melted at 85°C and stirred for 2 hours to obtain molten gallium-indium liquid metal. The liquid metal is then broken up by ultrasonic treatment for 45 minutes using a cell disruptor (ultrasonic power of 75%) to remove the surface oxide film from the molten gallium-indium liquid metal and form a uniformly dispersed gallium-indium alloy liquid metal.

[0050] Step 3: Mix epoxy resin (2.25 mm thick) and epoxy resin curing agent at a preset ratio of 2:1, then add the target ionic liquid and gallium-indium alloy liquid metal. Stir under ultrasonic conditions for 7.5 minutes until the mixture is completely obtained. The mass fraction of the target ionic liquid in the epoxy resin is 10%. The mass fraction of the gallium-indium alloy liquid metal in the epoxy resin is 50%.

[0051] Step 4: Pour the mixed solution into the mold and cure at room temperature for 10 hours. After demolding, the epoxy resin microwave absorbing composite material is obtained.

[0052] Example 2 A halide-type ionic liquid precursor with a molar ratio of 1:1.1 and a salt containing the target anion were dissolved in a solvent. After stirring at room temperature for 6 hours, the precipitate was removed by vacuum filtration to obtain a filtrate. The filtrate was then rotary evaporated at 30°C and vacuum dried at 90°C under a vacuum degree ≤0.01 MPa to remove the solvent, yielding the target ionic liquid. The halide-type ionic liquid precursor was 1-ethyl-3-methylimidazolium chloride. The salt containing the target anion was sodium p-toluenesulfonate. The solvent was methanol.

[0053] Step 2: Gallium particles and indium particles with a mass ratio of 2:1 are mixed, melted at 80°C and stirred for 0.5 h to obtain molten gallium-indium liquid metal. The liquid metal is then broken up by ultrasonic treatment for 60 min using a cell disruptor (ultrasonic power of 60%) to remove the surface oxide film of the molten gallium-indium liquid metal and form a uniformly dispersed gallium-indium alloy liquid metal.

[0054] Step 3: Mix epoxy resin (2.0 mm thick) and epoxy resin curing agent at a preset ratio of 2:1, then add the target ionic liquid and gallium-indium alloy liquid metal. Stir under ultrasonic conditions for 5 minutes until the mixture is completely obtained. The mass fraction of the target ionic liquid in the epoxy resin is 5%. The mass fraction of the gallium-indium alloy liquid metal in the epoxy resin is 40%.

[0055] Step 4: Pour the mixed solution into the mold and cure at room temperature for 8 hours. After demolding, the epoxy resin microwave absorbing composite material is obtained.

[0056] Example 3 A halide-type ionic liquid precursor with a molar ratio of 1:1.15 was dissolved in a solvent with a salt containing the target anion. After stirring at room temperature for 10 hours, the precipitate was removed by vacuum filtration to obtain a filtrate. The filtrate was then rotary evaporated at 35°C and vacuum dried at 100°C under a vacuum degree ≤0.01 MPa to remove the solvent, yielding the target ionic liquid. The halide-type ionic liquid precursor was one of N-methylimidazolium chlorides. The salt containing the target anion was sodium methanesulfonate. The solvent was anhydrous acetonitrile.

[0057] Step 2: Gallium particles and indium particles with a mass ratio of 4:1 are mixed, melted at 90°C and stirred for 1 hour to obtain molten gallium-indium liquid metal. The liquid metal is then broken up by ultrasonic treatment for 30 minutes using a cell disruptor (ultrasonic power of 90%) to remove the surface oxide film from the molten gallium-indium liquid metal and form a uniformly dispersed gallium-indium alloy liquid metal.

[0058] Step 3: Mix epoxy resin (2.5 mm thick) and epoxy resin curing agent at a preset ratio of 2:1, then add the target ionic liquid and gallium-indium alloy liquid metal. Stir under ultrasonic conditions for 10 minutes until the mixture is completely obtained. The mass fraction of the target ionic liquid in the epoxy resin is 20%. The mass fraction of the gallium-indium alloy liquid metal in the epoxy resin is 60%.

[0059] Step 4: Pour the mixed solution into the mold and cure at room temperature for 12 hours. After demolding, the epoxy resin microwave absorbing composite material is obtained.

[0060] Examples 1-1 to 1-10 Examples 1-4 are the same as Example 1 above. Examples 1-1 to 1-3, 1-5 to 1-10 are the same as Example 1 in terms of method, except that the process parameters are different, as shown in Table 1.

[0061] Table 1. Process parameters for Examples 1-1 to 1-10

[0062] In Table 1, IL1, IL2, and IL3 are 1-butyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, and 1-ethyl-3-methylimidazolium dicyandiamide, respectively.

[0063] The epoxy resin microwave absorbing composite materials prepared by the methods in Examples 1-1 to 1-10 were characterized as follows: 1.1 Morphological Characterization Scanning electron microscope (SEM) images of the epoxy resin microwave absorbing composite materials prepared by the method in Example 1 (Examples 1-4) are shown below. Figure 1 As shown. Figure 1 The spherical particles are gallium-indium alloy liquid metal, from Figure 1 It can be seen that the gallium-indium alloy liquid metal is well dispersed in the epoxy resin microwave absorbing composite material.

[0064] 2. Resistance value test 2.1 Resistance testing of epoxy resins containing different fillers The resistivity of the epoxy resin microwave absorbing composite materials prepared by the methods in Examples 1-1, 1-2, 1-3 and 1-4 (Example 1) is as follows: Figure 2 As shown. From Figure 2 It can be seen that pure epoxy resin materials (Examples 1-1) have excellent insulation properties, and their resistance values ​​can reach [value missing]. At room temperature, it has almost no electrical conductivity. The resistivity of the composite material doped with the target ionic liquid is reduced (Examples 1-2). The resistivity of the composite material doped with gallium-indium alloy liquid metal is greatly reduced (Examples 1-3), and the resistivity of the samples doped with both gallium-indium alloy liquid metal and the target ionic liquid is also greatly reduced (Examples 1-4).

[0065] 2.2 Resistance testing of composite materials of gallium-indium alloy liquid metal with different mass fractions Resistance values ​​were tested for Examples 1-4, 1-5, and 1-6, and their resistivity is as follows: Figure 3 As shown, while ensuring the quantitative determination of the target ionic liquid, the content of gallium-indium alloy liquid metal in the epoxy resin was varied. It was found that the resistivity of the epoxy resin microwave absorbing composite material decreased with increasing gallium-indium alloy liquid metal content. The resistivity reached its minimum when the gallium-indium alloy liquid metal content was around 60%.

[0066] 2.3 Resistance testing of different halide-type ionic liquid precursors The resistance values ​​of Examples 1-4, 1-9, and 1-10 are as follows: Figure 4 As shown, from Figure 4 It can be concluded that there is no significant difference in resistivity when different types of halide-type ionic liquid precursors are added to epoxy resin.

[0067] 3. Maximum Reflection Loss Test 3.1 Microwave Absorption Test of Epoxy Resins Containing Different Fillers Absorption tests were performed on Examples 1-1, 1-2, 1-3, and 1-4, and their maximum reflection loss was measured. The results are as follows: Figure 5 As shown.

[0068] The epoxy resins and epoxy resin microwave absorbing composites prepared in Examples 1-1, 1-2, 1-3, and 1-4 were tested for their microwave absorption function using a vector network analyzer. The specific method is as follows: The aforementioned epoxy resin and epoxy resin microwave absorbing composite material were processed into a coaxial ring with an outer diameter of 7.05 mm, an inner diameter of 3.05 mm, and a thickness of 2.2 mm. The microwave absorption efficiency of the material was tested using the coaxial method, and the results are as follows. Figure 5 As shown. Example 1-1: The epoxy resin itself does not have microwave absorption capabilities; therefore, its maximum reflection loss (calculated with a sample thickness of 3.5 mm) is only -3.5 dB. Example 1-2: This sample contains only the target ionic liquid, and its microwave absorption performance is improved, with a maximum reflection loss reaching -26.5 dB. Example 1-3: This sample contains only gallium-indium alloy liquid metal, which also has some microwave absorption performance, with a maximum reflection loss reaching -33.2 dB. Example 1-4 exhibits the best microwave absorption performance compared to all previous examples, with a maximum reflection loss of -51.3 dB.

[0069] 3.2 Microwave Absorption Test of Composite Materials with Different Mass Fractions of Gallium-Indium Alloy Liquid Metal Absorption tests were performed on Examples 1-4, 1-5, and 1-6, and the results are as follows: Figure 6 As shown, the maximum reflection loss is significantly reduced when epoxy resin is doped with gallium indium alloy liquid metal. With increasing gallium indium alloy liquid metal content, the reflection loss value first decreases and then increases, reaching its minimum in the optimal range.

[0070] 3.3 Microwave Absorption Test of Composite Materials with Target Ionic Liquids of Different Mass Fractions Absorption tests were performed on Examples 1-4, 1-7, and 1-8, and the results are as follows: Figure 7 As shown, under the condition of the same gallium-indium alloy liquid metal content, the changes in microwave absorption performance were tested by adding target ionic liquids with different mass fractions. Figure 7 It can be seen that the introduction of the target ionic liquid increases the microwave absorption performance of the composite material to a certain extent, and the maximum reflection loss of each component decreases to varying degrees as the mass fraction of the ionic liquid changes.

[0071] 4. Test of the real and imaginary parts of the average dielectric parameter 4.1 Tests of the real and imaginary parts of the average dielectric parameters of epoxy resins containing different fillers To more intuitively analyze the microwave absorption performance of epoxy resin composite materials with different fillers, the real and imaginary parts of the average dielectric parameter in Examples 1-1, 1-2, 1-3, and 1-4 at frequencies ranging from 2 to 18 GHz were calculated. The results are as follows: Figure 8 As shown, the average dielectric parameter of pure epoxy resin (Example 1-1) has both real and imaginary parts at very small values, indicating that pure epoxy resin does not have microwave absorption capability. The dielectric parameters of the samples with added target ionic liquid (Example 1-2) and gallium indium alloy liquid metal (Example 1-3) are improved. The samples with added target ionic liquid and gallium indium alloy liquid metal (Example 1-4) have the largest node parameters, indicating the best microwave absorption performance.

[0072] 4.2 Tests of the real and imaginary parts of the average dielectric parameters of gallium-indium alloy liquid metals with different mass fractions The real and imaginary parts of the average dielectric parameter in Examples 1-4, 1-5, and 1-6 at frequencies ranging from 2 to 18 GHz were calculated, and the results are as follows: Figure 9 As shown, with the increase of the liquid metal content of the gallium-indium alloy, the real and imaginary parts of the average dielectric parameter of the sample show a trend of first increasing and then decreasing, reaching a maximum value at around 50%.

[0073] 4.3 Test of the real and imaginary parts of the average dielectric parameters of target ionic liquids with different mass fractions The real and imaginary parts of the average dielectric parameter in Examples 1-4, 1-7, and 1-8 at frequencies ranging from 2 to 18 GHz were calculated, and the results are as follows: Figure 10 As shown, with the increase of the target ionic liquid content, the real and imaginary parts of the average dielectric parameter of the sample show a gradual increasing trend.

[0074] 5. Mechanical property testing Tensile strength test of epoxy resins containing different fillers Tensile strength tests were performed on Examples 1-1, 1-2, 1-3, and 1-4, and the results are as follows: Figure 11 As shown, the epoxy resin (Example 1-1) exhibits a certain mechanical strength. Under the condition of doping only with the target ionic liquid (Example 1-2), its tensile strength is higher than that of the epoxy resin matrix. After doping only with gallium-indium alloy liquid metal (Example 1-3), the tensile strength is lower than that of the epoxy resin matrix. The composite material simultaneously doped with the target ionic liquid and gallium-indium alloy liquid metal has the highest tensile strength, indicating that the target ionic liquid has the effect of improving the uneven dispersion of fillers.

[0075] The various embodiments in this specification are described in a progressive manner. For the same or similar parts between the various embodiments, please refer to each other. Each embodiment focuses on describing the differences from other embodiments.

[0076] The above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit this application. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of this application.

Claims

1. A method for preparing an epoxy resin wave-absorbing composite material, characterized in that, include: The precursor of the halide-type ionic liquid and the salt containing the target anion are dissolved in a solvent. After stirring at room temperature for 6-10 hours, the precipitate is removed to obtain a filtrate. The solvent is removed from the filtrate to obtain the target ionic liquid. Gallium particles and indium particles are blended and melted at 80~90℃ for 0.5~2h to obtain molten gallium-indium liquid metal. The surface oxide film of the molten gallium-indium liquid metal is removed to form a uniformly dispersed gallium-indium alloy liquid metal. Epoxy resin and epoxy resin curing agent are mixed in a preset ratio, and then the target ionic liquid and the gallium indium alloy liquid metal are added. The mixture is stirred under ultrasonic conditions for 5 to 10 minutes until it is completely mixed to obtain a mixed solution. The mixed solution was poured into a mold and cured at room temperature for 8-12 hours. After demolding, an epoxy resin microwave absorbing composite material was obtained.

2. The method for preparing the epoxy resin microwave absorbing composite material according to claim 1, characterized in that, The molar ratio of the halide-type ionic liquid precursor to the salt containing the target anion is 1:(1.1~1.2).

3. The method for preparing the epoxy resin microwave absorbing composite material according to claim 1, characterized in that, The mass ratio of the gallium particles to the indium particles is (2~4):

1.

4. The method for preparing the epoxy resin microwave absorbing composite material according to claim 1, characterized in that, The mass fraction of the target ionic liquid in the epoxy resin is 5% to 20%.

5. The method for preparing the epoxy resin microwave absorbing composite material according to claim 1, characterized in that, The mass fraction of the gallium-indium alloy liquid metal in the epoxy resin is 40% to 60%.

6. The method for preparing the epoxy resin microwave absorbing composite material according to any one of claims 1 to 5, characterized in that, The halide-type ionic liquid precursor is one of 1-butyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-ethyl-3-methylimidazolium dicyandiamide, 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, and N-methylimidazolium chloride.

7. The method for preparing the epoxy resin microwave absorbing composite material according to any one of claims 1 to 5, characterized in that, The salt containing the target anion is one of sodium bis(trifluoromethanesulfonyl)imide, sodium p-toluenesulfonate, and sodium methanesulfonate.

8. The method for preparing the epoxy resin microwave absorbing composite material according to any one of claims 1 to 5, characterized in that, The solvent is one of deionized water, methanol, and anhydrous acetonitrile.

9. An epoxy resin microwave absorbing composite material, characterized in that, The epoxy resin microwave absorbing composite material is prepared by the preparation method of any one of claims 1 to 8.

10. The application of the epoxy resin absorbing composite material according to claim 9 in the field of electromagnetic shielding of electronic equipment, absorbing materials and aerospace stealth coatings.